An Evaluation of the “Nawatwithi OTOP” Community Tourism in Sakon Nakhon Province - Bootcharee, Adjima; Lowatcharin, Grichawat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study the performance of the OTOP Nawatwithi tourism project of the participating villages in the provinces of Sakon Nakhon, 2) to study the assessment guidelines for the OTOP Nawatwithi Tourism Community Project in the area. Sakon Nakhon Province by the CIPP Model. The researcher employed a mixed methods research design by collecting quantitative data questionnaires from a survey of 200 people and collecting qualitative data via in-depth interviews of 12 key informants. The statistics used in the research were mean and standard deviation. The research results showed that : 1. Performance of the OTOP Nawatwithi Tourism Community Project in the Area Sakon Nakhon Province Are ready to join the project the villages were supported by multiple sectors and willing to participate in the project. In terms of inputs, the government provided sufficient funds, materials, and personnel supports. In terms of process, the communities received standardized packaging and tourism operation training, while government officers provided monitoring and assessment on a regular basis. In terms of product. 2. Guidelines for improvement towards the development of the OTOP Nawatwithi community tourism project in the area Sakon Nakhon Province participating entrepreneurs applied knowledge gained from the trainings to product development and community tourism in their villages.For further development, it is recommended that the government officers need to perform regular follow-up monitoring on the quality of packaging. In addition, the communities need to take care of the environment by collaborating with local leaders, villagers, and local authorities. Furthermore, government officers need to provide information and knowledge to enhance product quality and sales improvements through online platforms, and promotional activities.